2017
DOI: 10.1088/1361-6560/aa5fa2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dosimetric impact of system specific geometric distortion in an MRI only based radiotherapy workflow for prostate

Abstract: Dosimetric errors in a magnetic resonance imaging (MRI) only radiotherapy workflow may be caused by system specific geometric distortion from MRI. The aim of this study was to evaluate the impact on planned dose distribution and delineated structures for prostate patients, originating from this distortion. A method was developed, in which computer tomography (CT) images were distorted using the MRI distortion field. The displacement map for an optimized MRI treatment planning sequence was measured using a dedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 41 publications
3
54
0
Order By: Relevance
“…Geometrical distortions stemming from system related effects such Table 3 Statistical analysis of the PTV mean dose differences between scanners with least significant difference (LSD) for the generalized model, p-values <0.05 are presented in bold. as gradient non-linearity or B 0 field inhomogeneities should be evaluated before introducing a clinical MRI-only workflow [37]. Additional artifacts can derive from patient induced distortions, such as susceptibility and chemical shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrical distortions stemming from system related effects such Table 3 Statistical analysis of the PTV mean dose differences between scanners with least significant difference (LSD) for the generalized model, p-values <0.05 are presented in bold. as gradient non-linearity or B 0 field inhomogeneities should be evaluated before introducing a clinical MRI-only workflow [37]. Additional artifacts can derive from patient induced distortions, such as susceptibility and chemical shift.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that with geometric accuracy better than 2 mm within the entire FOV it is possible to achieve clinically feasible dose calculation accuracy for MRI-only RTP [21,23,[38][39][40][41]. The geometric accuracy of the applied MR platforms was sufficient for MRI-only RT [10,11,21,23,37]. An MRI-only approach is feasible and utilized internationally in few clinics for radiotherapy of the prostate employing either commercial or in-house sCT techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The system-related distortion has been reduced significantly by recent development on MRI hardware and software and the patient-induced distortion can be minimized by appropriate sequence parameters. The geometric accuracy achieved by recently installed MR platforms is acceptable for RT planning [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…detected up to 2 mm geometric distortion for a range of radial distances up to approximately 135 mm by performing rigid spatial co‐registration between MR and CT images, and investigated the dosimetric uncertainties caused by spatial offsets of 0.5 up to 3 mm to the target locations. Christian et al . measured a displacement map by detecting the difference of markers in the phantom between MR and CT images, and evaluated the dosimetric uncertainties for prostate patient by applying the displacement map to CT images.…”
Section: Discussionmentioning
confidence: 99%